Reduction of the Monounsaturated Fatty Acid Content of Escherichia Coli Results in Increased Resistance to Oxidative Damage - Vasquez-Guzman, C; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Reyes-Cerpa, S (2012)
Sin Editorial Disponible